Factors associated with parental resolution of a child's autism diagnosis: A systematic review - Naicker, Vrinda V.; Bury, Simon M.; Hedley, Darren (Frontiers in Psychiatry, 2023)
Background Receiving a child's autism diagnosis can be stressful; as such, parent resolution contributes to the wellbeing and development of healthy parent-child relationships. In other significant childhood diagnoses (e.g., cerebral palsy, diabetes), the degree to which parents adjust to (a) their child's diagnosis and (b) their changes in expectations concerning their child's development and capacity (referred to as resolution to diagnosis), has been associated with improved outcomes including facilitating parent-child relationships and improved parental wellbeing. Given potential benefits to parent and child, and the heterogenous nature of autism, examining the unique factors associated with resolution to diagnosis is important. In this systematic review we identified factors that support or inhibit parental resolution to their child receiving a diagnosis of autism. Methods We completed a systematic review following PRISMA guidelines of peer-reviewed studies from 2017 to 2022, that investigated parental resolution or acceptance of an autism diagnosis. Papers including “acceptance” needed to encompass both accepting the diagnosis and the implications regarding the child's abilities. We searched six databases (Scopus, Web of Science, MEDLINE, PsycINFO, ProQuest), with additional papers located following review of reference lists. Results Fourteen papers with 592 participants that investigated parental resolution or acceptance of an autism diagnosis, were included. We identified six common factors that facilitate or inhibit parental resolution and acceptance of an autism diagnosis including: symptom severity; religion, belief, and culture; knowledge and uncertainty; negative emotions (i.e., denial, shame, guilt); positive emotions; and support. Greater resolution was associated with improved “attunement and insightfulness” in the parent-child relationship. Limitation The review was limited by the small number of studies meeting inclusion criteria. Second, the quality of included studies was mixed, with over half of the studies being qualitative and only one randomized control trial (RCT) identified. Conclusion Parental resolution can have an impact on parent's perception of their child's capabilities and impact the parent-child relationship. We identified six categories that aid in inhibiting or promoting resolution to diagnosis. Despite taking a broad approach on the definition of resolution, the low number of studies identified in the review indicates a need for more research in this area. Systematic review registration http://www.crd.york.ac.uk/PROSPERO/, PROSPERO [ID: CRD42022336283].